Proteomics analysis of human serum of patients with non‐small‐cell lung cancer reveals proteins as diagnostic biomarker candidates. Issue 12 (10th June 2019) - Boccellino, Mariarosaria; Pinto, Federica; Ieluzzi, Vincenzo; Giovane, Alfonso; Quagliuolo, Lucio; Fariello, Chiara; Coppola, Mario; Carlucci, Annalisa; Santini, Mario; Ferati, Kenan; Bexheti‐Ferati, Arbëresha; Giordano, Antonio; et al.
Abstract: Non‐small‐cell lung carcinomas (NSCLC) is the most common type of lung cancer and it has a poor prognosis, because overall survival after 5 years is 20–25% for all stages. Thus, it is extremely important to increase the survival rate in the early stages NSCLC by focusing on novel screening tests of cancer identifying specific biomarkers expression associated with a more accurate tumor staging and patient prognosis. In this study, we focused our attention on quantitative proteomics of three heavily glycosylated serum proteins: AMBP, α2 macroglobulin, and SERPINA1. In particular, we analyzed serum samples from 20 NSCLC lung adenocarcinoma cancer patients in early and advanced stages, and 10 healthy donors to obtain a relative quantification through the MRM analysis of these proteins that have shown to be markers of cancer development and progression. AMBP, α2 macroglobulin, and SERPINA1 were chosen because all of them possess endopeptidase inhibitor activity and play key roles in cancer. We observe a variation in the expression of these proteins linked to the stage of the disease. Therefore, we believe that proteins like α2 macroglobulin, αmicroglobulin/bikunin, and SERPINA1 could be useful biomarkers for early detection of lung cancer and in monitoring its evolution. Abstract : It is extremely important to increase the survival rate in the early stages non‐small‐cell lung carcinomas by focusing on novel screening tests of cancer identifying specific biomarkers expression associated with a more accurate tumor staging, and patient prognosis. We observe a variation in the expression of these proteins linked to the stage of the disease. Therefore, we believe that proteins like α2 macroglobulin, α microglobulin/bikunin, and SERPINA1 could be useful biomarkers for early detection of lung cancer and in monitoring its evolution.